Reaching vulnerable women through maternity waiting homes in Malawi. Issue 1 (24th October 2016) - Singh, Kavita; Speizer, Ilene; Kim, Eunsoo Timothy; Lemani, Clara; Phoya, Ann
Abstract: Objective: To determine whether two maternity waiting homes (MWHs) supported by the Safe Motherhood Initiative are reaching vulnerable women during the early phase of their implementation. Methods: A cross‐sectional interview‐based study was conducted among women who attended two centers in Malawi with attached MWHs (Area 25 Health Centre, Lilongwe; and Kasungu District Hospital, Kasungu). Between April and June 2015, exit interviews were conducted among MWH users and non‐users. Results: Compared with non‐users, MWH users at Area 25 were significantly more likely to report a prior spontaneous abortion (10/46 [21.7%] vs 5/95 [5.3%]; P =0.006) and to be in the lowest wealth quintile (4/87 [4.6%] vs 0/150; P =0.029). Although not significant, a greater percentage of MWH users at Kasungu District Hospital than non‐users had a prior stillbirth (6/84 [7.1%] vs 0/77) or spontaneous abortion (3/84 [3.6%] vs 2/77 [2.6%]), and were in the lowest wealth quintile (15/175 [8.6%] vs 5/141 [3.5%]). MWH users at Kasungu lived further from the hospital than did non‐MWH users, although the difference was not significant (mean 6.81±9.1 km vs 4.05±7.42 km; P =0.067). Conclusion: MWHs offer a promising strategy to reduce maternal mortality in Malawi and other low‐income countries. Abstract : Maternity waiting homes are reaching vulnerable women in Malawi and offer a promising approach to provision of key maternal health services and messages.